The influence of microbicidal components of essential oils on the properties of the cellulose and lignocellulose materials - Mikala, Ondřej; Milichovský, Miloslav; Gojný, Jan; Hájek, Matěj (Technická univerzita vo Zvolene, 2016)
Biological effects of essential oils are investigated for many years. This work is focused on exploring the influence of saturated vapours components of essential oils on the mechanical, optical and chemical properties of cellulose and lignocellulose materials. Diluted vapours of active ingredients of essential oils could be used in future to protect archives made of cellulose materials. For testing were chosen ingredients of essential oils, that showed the highest bactericidal activity. Saturated vapours of these components act on selected cellulose and lignocellulose materials for a predetermined time. From the mechanical properties were measured tensile strength, bending stiffness and compressive strength. Optical properties are represented by the colour difference ΔE and chemical properties by pH change.
Vliv mikrobicidních složek esenciálních olejů na vlastnosti celulózových a lignocelulózových materiálů
Keywords: lignocellulose materials; essential oils; bending stiffness; colour difference ΔE*; lignocelulózové materiály; esenciální oleje; tuhost; barvová odchylka ΔE*